Maternal age and body mass index at term: Risk factors for requiring an induced labour for a late-term pregnancy. (February 2019) - Ferrazzi, Enrico; Brembilla, Gloria; Cipriani, Sonia; Livio, Stefania; Paganelli, Andrea; Parazzini, Fabio
Abstract: Introduction: We investigated the role of body mass index (BMI) and maternal age on the risk of late-term induction, prolonged induction time and caesarean section (CS) after induction. Material and Methods: This is a retrospective, observational study. All women without any fetal or maternal pathological condition, uterine scars or any other indication for an elective caesarean birth and had a singleton foetus in the cephalic position at term were included. Results: A total of 4006 women had a spontaneous onset of labour and 612 were induced for a late-term pregnancy. Labour induction was significantly more common in overweight (Adj Odds Ratio (OR) 1.48 95%CI 1.22–1.78) and obese (Adj OR 1.63 95%CI 1.24–2.14) women. Among induced women, a BMI ≥ 30 was a risk factor for a prolonged induction time in both nulliparous (AdjOR 2.4, 95%CI 1.02–5.67) and multiparous women (AdjOR 4.24, 95%CI 1.02–17.6). A BMI > 25–29.9 was significantly associated with a prolonged induction time only in nulliparous women (AdjOR 1.86 95%CI 1.05–3.30). A CS was more frequent in overweight (AdjOR 1.74, 95% CI 1.052.89) and obese women (AdjOR 2.72, 95%CI 1.42–5.25). Nulliparous women ageed 30–34 years had an induction time longer than women <30 years (OR 2.04 95%CI 1.07–3.91). Conclusions: The results of this study suggest that a BMI > 25 kg/m2 at term of pregnancy is a risk factor for the induction of labour during a late-term pregnancy, a prolonged induction time and higher caesarean section rate.